THE EFFECT OF A COMBINATION OF FOOT BATH GINGER BOILING WATER AND SLOW DEEP BREATHING EXERCISES ON BLOOD PRESSURE REDUCTION IN HYPERTENSIVE PATIENTS - Rinawaty, Desy; Sulastyawati, Sulastyawati; Retnowati, Lucia (Journal of Applied Health Management and Technology, 2021)
High blood pressure is a disease where there is a drastic increase in blood pressure, where the increase in blood pressure is more than normal. The purpose of this study was to determine the effect of a combination of foot bath ginger boiling water and slow deep breathing on blood pressure reduction in hypertensive patients. The research design used in this study was Quasy experimental Design with a pre-test and post-test control group design research design, with non-probability sampling techniques, the sample size in this study was 44 respondents divided into 2 namely 22 treatment groups and 22 groups control. The treatment is carried out 6 times for 3 weeks in intensity 2 times a week. Each intervention will be conducted then the respondent will be measured pre-test, then post-test measurements will be carried out after the respondent gets foot bath ginger soak and slow deep breathing treatment. The results showed that after the foot bath treatment of ginger boiled water and slow deep breathing systolic and diastolic blood pressure changed by an average of 40.42%, and for systolic blood pressure was 125.00 mmHg, and diastolic blood pressure 79.55mmHg. The results of the study stated that there was an influence from the administration of the foot bath intervention of ginger cooking water and slow deep breathing on the decrease in blood pressure in hypertensive patients. This can be seen from the Wilcoxon test results with a P value = 0,000 or (p <Î± = 0.05). It can be concluded that the foot baths of ginger cooking water and slow deep breathing have an effect on reducing blood pressure in hypertensive patients. Foot Bath ginger boiling water with a combination of slow deep breathing is very good and suitable for hypertensive patients who choose to use treatment with therapeutic methods, where the therapy can widen blood vessels so that blood circulation becomes smooth so that blood pressure can drop.